An Inquiry-Based Learning on Salt Hydrolysis and Buffer Solutions in the Context of Christian Education - Rachel Veronica Putri Pniel Saragih; Year Rezeki Patricia Tantu; Dince Bunda (Diligentia: Journal of Theology and Christian Education, 2026)
Chemistry is often considered difficult and abstract, as well separate from the Christian faith. One Christian school in Jakarta that incorporates Christian values into its vision and mission, has not yet been able to provide learning that integrates Biblical Christian perspectives, particularly in Chemistry lessons. The diverse contexts is of 11th-grade students, including 13 boys and 11 girls. This study aims to examine inquiry-based learning on the topic of salt hydrolysis and buffer solutions within the context of Christian education. Inquiry-based learning is not only viewed as a means of knowledge construction but also to admire the greatness and order of God’s creation through the principle of equilibrium in the topics of hydrolysis and buffer solutions. This study began with observation, lesson planning, implementation of learning, analysis of learning outcomes, and final reflection. Data were taken from test scores, student worksheet results, project results, and reflections, then processed using simple statistics and explained qualitatively. The results of reflection showed that inquiry learning was able to provide a deeper understanding of the concepts of hydrolysis and buffer solutions, real and reflective applications of the knowledge learned, and student engagement through the inquiry process and group collaboration. This research is expected to provide a contribution to Christian educators in designing chemistry learning that is holistic and transformative.